Traditional medicine in Wartair, District Malakand, Pakistan: An ethnomedicinal study of locally used plants - Haseen Ullah, Haseen Ullah; Ibrahim, Muhammad; Sara, Sara; Sadaf Bibi, Sadaf Bibi; Shaha Buddin, Shaha Buddin; Ullah, Mohsin; Huma Zareef, Huma Zareef (Ethnobotany Research and Applications, 2025)
Background: The purpose of this study was to explore the utilization and cultural significance of medicinal plants in ethnomedicinal practices among local communities of Wartair, District Malakand, Pakistan. The local people in the study area largely depend on indigenous medicinal plants for their essential healthcare needs. Methods: This ethnomedicinal study involved regular field trips and discussions with approximately 130 native informants from the study region, representing diverse socio-economic and educational backgrounds. Information was gathered through interviews and semi-structured questionnaires, emphasizing the perspectives of indigenous people. Data analysis employed quantitative indices, including Informant Consensus Factor (ICF) and Fidelity Level (FL %). Results: This survey comprehensively documented 50 medicinally important plants belonging to 48 genera and 28 families. The findings indicated that herbs dominated (52%) among the collected plants, followed by shrubs (26%) and trees (22%). The collected plants were predominantly perennials (62%), followed by annuals (34%) and biennials (4%). The study revealed that the maximum Informant Consensus Factor (ICF) values were for cardiovascular diseases (0.82), sore throat disease (0.81), and skin disease (0.70). Acacia modesta L., Cannabis sativa L., and Ricinus communis L. emerged as the most significant and extensively used species, with Fidelity Level (FL) values of 94.5%, 92.3%, and 89.28%, respectively. Conclusion: This study noted that Wartair District Malakand, Pakistan, has rich biodiversity in medicinal plants, which are crucial for the fundamental healthcare requirements of the local inhabitants, particularly the underprivileged. Keywords: Ethnobotany, Medicinal Plants, Informant Consensus Factor, Fidelity level, Malakand, Pakistan